1987
DOI: 10.4315/0362-028x-50.1.62
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus cereus Contamination of Seeds and Vegetable Sprouts Grown in a Home Sprouting Kit

Abstract: Sprouting seeds (alfalfa, mung bean and wheat) were purchased at local health food stores and examined for Bacillus cereus by the official AOAC method. Of 98 units collected, 56 (57%) were positive for B. cereus at levels ranging from 3 to >500 per g. Population levels of B. cereus on sprouts grown from naturally contaminated seeds in a home sprouting kit ranged from a mean of log10 3.72 for alfalfa to 5.39 for wheat; the log10 mean for mung bean sprouts was 4.52. Washing contaminated sprouts for 10 min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
0

Year Published

1988
1988
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(20 citation statements)
references
References 0 publications
0
20
0
Order By: Relevance
“…Finally, the alfalfa sprouts eaten by Ameri-3 -5 orders of magnitude per gram during sprouting of experimentally inoculated seed. The same phenomenon has been obcan and Finnish case-patients were produced by many different growers but were grown from seed from a single common served for Bacillus cereus, which caused an outbreak of food poisoning linked to home-sprouted vegetable sprouts [20,21]. source -a seed shipper in the Netherlands -indicating that the seed was contaminated before it was shipped.…”
Section: Resultsmentioning
confidence: 81%
“…Finally, the alfalfa sprouts eaten by Ameri-3 -5 orders of magnitude per gram during sprouting of experimentally inoculated seed. The same phenomenon has been obcan and Finnish case-patients were produced by many different growers but were grown from seed from a single common served for Bacillus cereus, which caused an outbreak of food poisoning linked to home-sprouted vegetable sprouts [20,21]. source -a seed shipper in the Netherlands -indicating that the seed was contaminated before it was shipped.…”
Section: Resultsmentioning
confidence: 81%
“…Alfalfa sprouts sold for consumption constitute such an environment, since production of the sprouts takes place at temperatures and humidity conditions that are favorable for bacterial growth, and it is known that raw sprout products contain a high number of bacteria (10,24). The same is true for sprouts that are cultivated at home by the consumer from seeds sold for this purpose (15). The bacteria present on sprout products originate from those colonizing the seeds and are thus predominantly rod-shaped soil microorganisms (10).…”
mentioning
confidence: 78%
“…In another study examining the microbial quality of sprouting seeds, Bacillus cereus was found in 56 of 98 sprouting kits purchased. When seeds from contaminated kits were sprouted, contamination rose to a mean level of 3.72 log 10 CFU/g for alfalfa sprouts and 4.53 log 10 CFU/g for mung bean sprouts (17). Investigation of seed sprouts in Norway found thermotolerant coliform bacteria in 24% of 300 samples, and E. coli was isolated from 8 samples.…”
mentioning
confidence: 99%
“…These outbreaks have been most commonly associated with alfalfa sprouts but have also been linked to clover, radish, and mung bean sprouts. One of the earliest reports of illness associated with sprouts was in 1973, when an outbreak of Bacillus cereus occurred due to contaminated home sprouting kits (17). Reported outbreaks have increased steadily in the intervening decades (32).…”
mentioning
confidence: 99%